Effective field theory and integrability in two-dimensional Mott transition - Bottesi, Federico L. (2010)
Fil: Zemba, Guillermo Raúl. Pontificia Universidad Católica Argentina. Facultad de Ciencias Fisicomatemáticas e Ingeniería; Argentina